THE BENEFIT OF STRUCTURED ACTIVITY IN WOMEN WITH PREDIABETES - Eliana, Fatima (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION To determine the effect of structured physical activity on decreasing body fat, increasing muscle mass, decreasing HbA1c and LDL cholesterol levels and increasing HDL cholesterol. METHODOLOGY The research method is pre-experimental one group pretest posttest design. Subjects were told to conduct structured activities in gymnastics room of at least 60 minutes, 3 times a week, for 6 months. Research subjects were women aged 18-60 years who were members of Persadia gymnastics at the Islamic Hospital Pondok Kopi Jakarta. Examination of body fat and muscle mass percentage was done using the Bioelectrical Impedance Analysis (BIA) tool. Examination of serum HbA1c, LDL and HDL was done using the ELISA method. RESULTS This study initially included 80 subjects but there were 8 people who dropped out, statistical calculations were only carried out on 72 subjects. The results of this study showed a decrease in the average percentage of body fat by 0.526% (P=0.15), an increase in the average percentage of muscle mass by 24.6% (P=0.02), decrease in HbA1c of 0.2% (p=0.22) and LDL levels of 13 mg / dL (p=0.61) and an increase in HDL of 12 mg/dL (p=0.05). CONCLUSION Structured physical activity for at least 60 minutes, 3 times a week, for 6 months in women with prediabetes can increase muscle mass and HDL cholesterol levels. Structured physical activity was also beneficial in reducing body fat, HbA1c and LDL cholesterol in several research subjects, but it was not statistically significant.